2016
DOI: 10.1097/iae.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Internal Limiting Membrane Peeling on Macular Hole Reopening

Abstract: The results of this meta-analysis support the concept that ILM peeling during macular hole surgery reduces the likelihood of macular hole reopening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 60 publications
(62 reference statements)
4
46
0
Order By: Relevance
“…[60][61][62] In a recent large meta-analysis of 5480 cases, Rahimy and McCannell concluded that ILM peeling at the time of surgery significantly reduces the likelihood of the hole reopening but without better postoperative best-corrected visual acuities. 63 (I++, Good quality, Strong recommendation) 65 Brooks et al reported an 18% difference in favor of ILM peeling with a statistically significant difference in visual acuity between the peeling and non-peeling groups. 66 Interestingly, they noted a rather high rate (25%) of macular holes reopening in the non-peeled eyes compared with no reopening in ILM peeled macular holes.…”
Section: P189mentioning
confidence: 99%
See 2 more Smart Citations
“…[60][61][62] In a recent large meta-analysis of 5480 cases, Rahimy and McCannell concluded that ILM peeling at the time of surgery significantly reduces the likelihood of the hole reopening but without better postoperative best-corrected visual acuities. 63 (I++, Good quality, Strong recommendation) 65 Brooks et al reported an 18% difference in favor of ILM peeling with a statistically significant difference in visual acuity between the peeling and non-peeling groups. 66 Interestingly, they noted a rather high rate (25%) of macular holes reopening in the non-peeled eyes compared with no reopening in ILM peeled macular holes.…”
Section: P189mentioning
confidence: 99%
“…[104][105][106][107][108][109][110] Longer positioning may be required for holes larger than 400 µm or those with inadequate gas fill. 63,108 A small comparative study was published comparing facedown positioning to not being face down and found that differences in positioning had no effect on the macular hole closure rate. 111 In all of these studies, however, the patient was told to avoid the face-up or supine positioning.…”
Section: P189mentioning
confidence: 99%
See 1 more Smart Citation
“…36 Late hole re-opening A recent meta-analysis of 5,480 FTMH surgeries among 50 publications has shown a significantly lower rate of FTMH reopening after ILM peeling than in surgery without ILM peeling. 22 Specifically, the reopening rate without ILM peeling was 7.12% compared with 1.18% with ILM peeling (odds ratio: 0.16; 95% confidence interval: 0.11-0.22, p<0.0001). 22 2) Retinal consequences of ILM peeling ILM peeling is a challenging surgical procedure and has a number of potential detrimental consequences not least of which relate to the surgeon learning curve.…”
Section: ) Macular Hole Closurementioning
confidence: 89%
“…21 ILM peeling has gained widespread acceptance, since it has been shown to improve closure rates and prevent late postoperative reopening, one of the most common complications of successfully closed MH. 20,22,23 However, some authors argue against ILM peeling, since it may cause iatrogenic damage, result in a number of changes in retinal structure and visual function, and may not be necessary in all cases. The extent of ILM peeled during surgery, the technique of ILM peeling, and several variants of how the ILM is peeled have been described.…”
Section: Introductionmentioning
confidence: 99%